Effect of Different Conditions on Viability and Antagonistic Activity of Saccharomyces boulardii on Enteric Pathogenic Bacteria (Baghdad Science Journal, 2025)
In this part of programme , different bacterial isolates mainly Salmonella spp, Shigella spp and Escherichia coli were used for antagonism with Saccharomyces boulardii under different conditions . S.boulardii was grown under aerobic conditions and antagonized with young overnight nutrient broth cultures of test bacterial isolates and other kept in refrigerator for a week after full growth . Young cultures were more susceptible to antagonistic effect of yeast compared to old cultures and on isolates grown on solid medium for 24 hr. S.boulardii grown under aerobic and microaerobic conditions and antagonized with overnight broth cultures of test bacterial isolates , The results revealed that aerobic cultures of yeast had more inhibitory effect on test isolates .Concentration of yeast cells from liquid media GS( prepared from soluble fraction of gluten and mixed with equal volume of corn steep water and GS2%) was found not to be exceeded 109 yeast cell/ ml of suspension due to the large size of yeast cells .Effect of freezing on viability of yeast cells grown in GS and GS2% was negligible and there was no significant differences since the difference was less then half log cycle